Debris Flow Analysis and Susceptibility Mapping Using Flow-R - Aryal, Anish; Bohara, Binod; Bhattarai, Tulasi Ram; Aryal, Asmita (Journal of Engineering and Sciences, 2025)
Debris flow poses a significant challenge, mostly in hilly areas of Nepal. Despite the frequency and devastation caused by such events, accurately predicting debris flow paths and their impact remains a major difficulty. The present study addresses this critical problem by utilizing the Flow-R model, an empirical, open-source tool ideal for constrained resources. Through debris flow modelling and hazard mapping, this study investigates the Ramtola landslide area located in Baglung Municipality. A combination of methods is employed, including Flow-R path prediction, field-based susceptibility mapping, and GIS-based analysis. By integrating these three approaches, this study provides a relatively accurate assessment of debris flow hazard. The results demonstrate that this comprehensive methodology can significantly enhance risk evaluation and mitigation strategies in debris flow-prone areas.